Quality Analysis of Congenital Hypothyroidism Screening (CHS) Implementation in Newborns by Independent Midwives: A Review of Sample Collection Time, Specimen Quality, and Speed of Follow-up Results - Ummah, Kholifatul; Imeldawati, Rakhmalia; Kustini, Kustini; Susila, Ida (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2025)
This descriptive analytical cross-sectional study assessed the quality of Congenital Hypothyroidism Screening (CHS) implementation by Independent Midwives, a vital program for preventing intellectual developmental delay caused by congenital hypothyroidism (CH). The study involved 60 newborns at BPM Kustini, Lamongan (January-June 2025). Quality was evaluated across three critical points: timeliness of sample collection, quality of Dried Blood Spot (DBS) specimens, and speed of follow-up on results. The findings indicated that 66.67percent of samples were collected on time (48-72 hours), 75percent of DBS specimens were of good quality, and 83.33percent of follow-up results were conducted quickly (less than equals 10 days). Bivariate analysis using the Chi-Square test revealed significant correlations between the timeliness of sampling and the quality of DBS specimens (p equal 0.002) and between specimen quality and the speed of follow-up results (p equal 0.003). Overall, the quality of CHS in independent midwifery practices was promising. Timeliness of sample collection was found to be key to producing high-quality DBS specimens, which, in turn, affected the speed of result follow-up. The study recommends improving midwives' technical competence and family education, and strengthening the referral system to reinforce CHS's success in community services.